2017
DOI: 10.1097/txd.0000000000000724
|View full text |Cite
|
Sign up to set email alerts
|

Influence of HLA Matching on the Efficacy of Allogeneic Mesenchymal Stromal Cell Therapies for Osteoarthritis and Degenerative Disc Disease

Abstract: BackgroundThe necessity for more effective therapies for chronic osteoarticular diseases has led to the development of treatments based on mesenchymal stem cells (MSCs), the natural precursors of musculoskeletal tissue. Treatments with autologous MSCs yielded excellent results, with nearly 70% improvement of pain and disability in osteoarthritis and degenerative disc disease. Using allogeneic MSCs is logistically more convenient and would widen the pool of eligible patients, but potential immune rejection shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 14 publications
2
61
1
Order By: Relevance
“…There is the lack of studies comparing effects of matched vs. mismatched MSCs in the large animal model of sepsis. However, the clinical study of the team of Garcia-Sancho (34) showed that better HLA matching of donor MSCs with recipients did not enhance the efficacy of MSCs therapy in osteoarthritis and degenerative disc disease. Furthermore, there are several completed clinical trials applying allogenic MSC without any analysis of donor MSCs and recipient matching (5,(35)(36)(37) indicating that the donor MSCs and recipient matching may not play the role in MSCs potency.…”
Section: Discussionmentioning
confidence: 99%
“…There is the lack of studies comparing effects of matched vs. mismatched MSCs in the large animal model of sepsis. However, the clinical study of the team of Garcia-Sancho (34) showed that better HLA matching of donor MSCs with recipients did not enhance the efficacy of MSCs therapy in osteoarthritis and degenerative disc disease. Furthermore, there are several completed clinical trials applying allogenic MSC without any analysis of donor MSCs and recipient matching (5,(35)(36)(37) indicating that the donor MSCs and recipient matching may not play the role in MSCs potency.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been observed that the immunogenicity of ASCs decreases with cell passaging, so that cells at low passages are more immunogenic than those at higher passages (McIntosh et al, 2006), and that ASCs are not fully immune privileged, since they elicit both humoral and cellular immune response in vivo, depending on the microenvironment (Ankrum et al, 2014). Also ASC differentiation may alter their immunogenic phenotype, increasing HLA class-I and HLA class-II expression (García-Sancho et al, 2017), as well as culturing condition (e.g., use of human serum or serum-free conditions) (Patrikoski et al, 2014).…”
Section: The Road Ahead In Immunomodulatory Potential Of Ascsmentioning
confidence: 99%
“…Four clinical trials have been published that have documented the presence/absence of anti-HLA antibodies in patients after allo-MSC therapy for various disease indications, including osteoarthritis, Crohn’s disease, and Type II diabetes. Results published by Garcia-Sancho et al on the influence of HLA-matching on the efficacy of allogeneic MSC therapy in osteoarthritis and degenerative disk disease ( 43 ), indicated that only a very limited number of patients receiving MSC had developed anti-donor antibodies and, surprisingly, better donor–recipient HLA-matching did not enhance efficacy. In another clinical trial for complex perianal fistulas in Crohn’s disease, Panés et al reported that allogeneic adipose-derived mesenchymal stem cells (Cx601) treated patients developed donor-specific antibodies ( 44 ).…”
Section: Immunogenicity Of Human Msc In Human Subjectsmentioning
confidence: 99%
“…Alternative cell types could be investigated to replace damaged tissue ( 55 , 56 ), or in-depth studies into the mechanism of action of, e.g., licensed MSC may yield candidate molecules which could replace cell therapy altogether. Investigation of alternative routes of administration (e.g., “inert” locations such as the articular cavity or intervertebral disk ( 43 ) which may lower the “visibility” of the cells to the host immune system. A detailed understanding of how allo-MSC cell death affects their immunogenic or tolerogenic properties and how (or if) allo-MSC cell death regulates ensuing anti-donor immune responses.…”
Section: Perspectivementioning
confidence: 99%
See 1 more Smart Citation